Leveraging applications of formal methods, verification and validation. modeling : 8th International Symposium, ISoLA 2018, Limassol, Cyprus, November 5-9, 2018, Proceedings /: modeling : 8th International Symposium, ISoLA 2018, Limassol, Cyprus, November 5-9, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available